Discovery of a phylogenetically distinct poxvirus in diseased Crocodilurus amazonicus (family Teiidae) - Seitz, Kerstin (Arch Virol, 2021)
A novel poxvirus was discovered in Crocodilurus amazonicus (Teiidae) presenting with a debilitating skin disease. The generated first genome sequence of a reptilian poxvirus revealed the closest phylogenetic relationship to avipoxviruses, highlighting potential virus exchanges between avian and reptilian species. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00705-021-04975-6.